Refat Abduzhemilev - Refat Abduzhemilev (Крымское историческое обозрение)
The matter for consideration in the review is the translation of the chronicle “Seven Planets in the News about the Tatar kings” from Ottoman into Russian, made by I.R. Gibadullin and published as a continuation to the first transliteration-book by M.A. Usmanov Center for Research of the Golden Horde and Tatar Khanates of Marjani Institute of History of the Tatarstan Academy of Sciences. The translation is close to the original, it opens access to the content of the source and serves as an intermediate step for further work on the chronicle, which determines the significance of the translation. Some contradictory theses from the preface to the book are noted. The translation is analyzed from the perspective of form and content.